1993
DOI: 10.1111/j.1365-277x.1993.tb00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of food and nutrient intake in a suburb of Dublin with chronically high unemployment

Abstract: The diet‐history (7 typical recent days) method was used to determine patterns of food and nutrient intake in 50 families, randomly selected from the electoral register of a socially disadvantaged Dublin suburb. Some 66% of income was from unearned social security or other payments. Financial assistance was sought from money lenders by 11 of the 50 families. There was little evidence to suggest that nutrient intakes among males or among children were inadequate. Women, because of a low energy intake and a belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This approach recognizes the diverse needs of subgroups in the population, where advice on key food sources of nutrients in the overall national diet can have different outcomes in the sub-groups. For example, a low iron intake is prevalent among Irish women (Lee & Cunningham, 1990) -particularly those from socially disadvantaged backgrounds (Gibney & Lee, 1993). Advice to reduce fatty meat consumption to effect a reduction in fat intakes may be counter-productive for groups where this type of meat represents an important source of iron and leaner cuts are economically out of reach.…”
Section: Dietary Guidelines: Food Intakes: Irelandmentioning
confidence: 99%
“…This approach recognizes the diverse needs of subgroups in the population, where advice on key food sources of nutrients in the overall national diet can have different outcomes in the sub-groups. For example, a low iron intake is prevalent among Irish women (Lee & Cunningham, 1990) -particularly those from socially disadvantaged backgrounds (Gibney & Lee, 1993). Advice to reduce fatty meat consumption to effect a reduction in fat intakes may be counter-productive for groups where this type of meat represents an important source of iron and leaner cuts are economically out of reach.…”
Section: Dietary Guidelines: Food Intakes: Irelandmentioning
confidence: 99%
“…Studies of food expenditures have been conducted by some scholars, but the majority focuses on the composition of food consumed and its relationship with income [22,23], economic growth [24,25], as well as urbanization [5,[26][27][28][29][30][31][32]. In addition, other studies showed the relationship between food consumption composition with poverty [33][34][35] and unemployment [36][37][38][39][40] showing that both issues limit people's ability to consume more various and healthier food. It should be of concern that currently, the connection among regions has been increased extensively; thus, the flow of goods and people, including food products, has become more intense.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the amount of disposable income available for food and other necessities, after-shelter income (i.e., reported income minus costs paid for rent and basic utilities for the month) was adjusted for family size and composition by expressing this amount as a ratio of total daily energy requirement estimates for the family (Gibney and Lee 1993), using current age-and sex-specific estimates of average energy requirements (Scientific Review Committee 1990). An examination of the results of a series of diagnostic tests for collinearity in PROC REG indicated that multicollinearity was at most a minor source of error in the parameter estimates derived from these regression models.…”
Section: Methodsmentioning
confidence: 99%